Projecting the prevalence of obesity in South Korea through 2040: a microsimulation modelling approach - Young-Eun Kim; Seok-Jun Yoon; Yoon-Sun Jung; Dun-Sol Go (BMJ Open)
Objective To project the prevalence of obesity in 2040 among individuals 19 years and older in South Korea.Design, setting, and participants Using the ‘Population Health Model-body mass index’ (BMI) microsimulation model, the prevalence of obesity in Korean adults 19 years and older was projected until 2040. The model integrated individual survey data from the Korea Health Panel Survey of 2011 and 2012, population statistics based on resident registration, population projections and complete life tables categorised by sex and age. Birth rate, life expectancy and international migration were based on a medium growth scenario. The base population of Korean adults in 2012, devised through data aggregation, was 39 842 730. The prediction equations were formulated using BMI as the dependent variable; the individual’s sex, age, smoking status, physical activity and preceding year’s BMI were used as predictive factors.Outcome measure BMI categorised by sex.Results The median BMI for Korean adults in 2040 was expected to be 23.55 kg/m2 (23.97 and 23.17 kg/m2 for men and women, respectively). According to the Korean BMI classification, 70.05% of all adults were expected to be ‘preobese’ (ie, have BMIs 23–24.9 kg/m2) by 2040 (81.23% of men and 59.07% of women) and 24.88% to be ‘normal’.Conclusions We explored the possibility of applying and expanding on the concept of microsimulation in the field of healthcare by combining data sources available in Korea and found that more than half of the adults in this study population will be preobese, and the proportions of ‘obesity’ and ‘normal’ will decrease compared with those in 2012. The results of our study will aid in devising healthy strategies and spreading public awareness for preventing this condition.